The breakthrough of philosophy of mind in the construction of artificial intelligence concepts in Marxist philosophy - Xu Lan; Hao Shu (Trans/Form/Ação)
In the context of contemporary technology, artificial intelligence has become the focus of thinking and dialectics, reaching boundaries beyond the dimensions of technology and directly to the core of human existence and consciousness. Philosophy of mind, as an ancient and profound way of thinking, has encountered many obstacles in the construction of artificial intelligence concepts. Marxist philosophy emphasizes the determinism of matter and mode of production. From the perspective of Marxist philosophy, this study compares and analyzes the theoretical differences and complementarities between it and traditional philosophy of the mind, with the aim of providing a new perspective for the construction of artificial intelligence concepts and enriching their connotations. The study first conducts a conceptual analysis of Marxist philosophy and, then, proposes a supplement and transcendence of Marxist philosophy to the philosophy of mind based on the construction of artificial intelligence concepts. The research finds that a philosophical dialogue has been formed between artificial intelligence and historical materialism, which not only reveals how to understand artificial intelligence from the historical dimension, but also provides valuable philosophical guidance for people in this era full of opportunities and challenges. In the process of technological evolution, people must adhere to the bottom line of humanistic spirit and ensure that technology always serves the human beings’ comprehensive, free and balanced growth. In addition, in order to ensure that artificial intelligence technology truly serves the common well-being of mankind, people also need to constantly reflect on, adjust and improve the development and application of technology, and jointly promote social progress.